PENETAPAN KADAR RENDEMEN DAN FLAVONOID EKSTRAK DAUN KELOR (Moringa oleifera) SECARA SPEKTROFOTOMETRI UV-VIS - Whardhani, Sabrina K; Handayani, Indri Astuti; Loimalitna, Pricillya Maria; Chandra, Pra Panca Bayu; Christian, Yulius Evan (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Moringa leaves (Moringa oleifera L.) are herbal plants known to contain bioactive compounds such as flavonoids and phenolics, which have potential as natural antioxidants and can be utilized in the development of herbal-based pharmaceutical preparations. This study aimed to determine the organoleptic characteristics and the total flavonoid content of 96% ethanol extract of Moringa leaves. The extraction process was carried out using the maceration method with 96% ethanol solvent on 1 kg of fresh Moringa leaves. The leaves were dried into simplicia powder weighing 126.22 g, then macerated for 3 days with stirring every 24 hours. The filtrate was evaporated using a rotary evaporator at 40°C to obtain a thick extract, yielding 7.01% with a native DER value of 14.26. The organoleptic characteristics showed that the extract had the typical odor of Moringa leaves, a bitter taste, and a greenish-brown color. The determination of flavonoid content was conducted using the aluminium chloride colorimetric method with quercetin as the standard, and measurements were performed at a maximum wavelength of 450 nm. The calibration curve showed a linear relationship between quercetin concentration and absorbance with the regression equation y = 0.0163x – 0.0789 and R² = 0.9986. The analysis results showed that the total flavonoid content of the 96% ethanol extract of Moringa leaves was 1203.78 ± 2.98 mg/100 g. With its high flavonoid content, Moringa leaf extract has the potential to be developed as a natural antioxidant in herbal-based pharmaceutical formulations.